Botanical tour of Christian Art at the National Museum of Ancient Art (Lisbon, Portugal) - Carvalho, Luis (2020)
Christian works of art, from the middle XIV to early XIX centuries, were studied in order to contribute to a new perspective of the cultural history of plants in Portuguese and European art displayed at the National Museum of Ancient Art (NMAA). The symbolic use of trees, leaves, flowers and fruits in painting, sculpture and tapestry were compared with theological data from the Bible, Apocrypha Gospels and codes of symbols from the XVII to XX centuries, as well as pictorial data from academic literature and photographic databases. We found 40 botanical taxa used as symbols that aimed to reinforce moral teachings and theological allegories. This information makes the NMAA an extraordinary place to promote scientific culture and interdisciplinary studies on the role of plants in art and allowed the creation of a botanical tour of the collections. The data of our research can be used to create botanical tours in other museums as well as be helpful to those who guide visits in art museums. Thus, our research proposes a new agenda for art museums, highlighting routes that can be created by recovering the ancient symbolic meaning of plants. Decoding these hidden symbols can reveal significative messages to those engaged in religious tourism and pilgrimage.